Feature Properties of Photonic Crystal Fiber with Hollow Core Filled Nitrobenzene - Tran Quoc, Vu; Chu Thi Gia, Trang; Le Van, Minh; Nguyen Thi, Thuy; Nguyen Thi Hong, Phuong; Doan Quoc, Khoa; Dinh Xuan, Khoa; Le Xuan, Bao; Vo Thi Minh, Ngoc; Chu Van, Lanh (Communications in Physics, 2020)
In this paper, a photonic crystal fiber (PCF) with core infiltrated with Nitrobenzene is proposed and investigated. Its feature properties as the effective refractive index, effective mode area, chromatic dispersion, and confinement loss have been numerically simulated. The obtained results show that characteristic quantities of PCF with core infiltrated with Nitrobenzene (PCF-N) having some advantages in comparison to PCF with core infiltrated with Toluene (PCF-T) at 1.55μm wavelength. For the purpose of supercontinuum generation, two optimal structures with lattice constants 2.0μm and 2.5μm with filling factors d/Ʌ = 0.3 are identified.